The reality of informed consent at peruvian medical practice - Revilla Lazarte, Diana E. (2024)
Informed consent has great importance and significance, for both biomedical research and medical practice. Because of several reasons, the informed consent process is still being inadequately carried out in peruvian medical care, despite its incorporation in medical treatises. This article attempts to evaluate some of the factors involved. It provides a brief history of informed consent, followed by a contextual approach to current medical practice and a comparison of the ideal and real situations, discussing possible solutions and concluding that the informed consent should be based on respect for patients and a fair relationship of physicians with patients as equals.